Effects of dietary Clostridium butyricum supplementation on growth performance, intestinal development, and immune response of weaned piglets challenged with lipopolysaccharide - Chen, Ling (J Anim Sci Biotechnol, 2018)
BACKGROUND: Weanling pigs, with immature immune system and physiological function, usually experience post-weaning diarrhea. This study determined the effects of dietary Clostridium butyricum supplementation on growth performance, diarrhea, and immunity of weaned pigs challenged with lipopolysaccharide (LPS). METHODS: In Experiment (Exp.) 1, 144 weaned piglets were weaned at 21 d and randomly assigned to six groups, with six replicates per group and four pigs per replicate, receiving a control diet (CON) or diet supplemented with antibiotics (AB) or C. butyricum (CB) (0.1%, 0.2%, 0.4%, or 0.8%), respectively. All diets in Exp. 1 were a highly digestible basal diet, with 3,000 mg/kg zinc oxide supplied in the first 2 wk only. In Exp. 2, 180 piglets were weaned at 21 d and randomly assigned to five groups, with six replicates per group and six pigs per replicate, receiving CON, AB, or CB (0.2%, 0.4%, or 0.6%) diets. The digestibility of diets was lower than those in Exp. 1, and did not include zinc oxide. At 36 d of Exp. 2, 12 piglets were selected from each of the CON and 0.4% CB groups, six piglets were intraperitoneally injected with LPS (50 μg/kg body weight) and the other six piglets with normal saline; animals were killed at 4 h after injection to collect blood, intestine, and digesta samples for biochemical analysis. RESULTS: In Exp. 1, CB and AB diets had no effect on growth performance of piglets. In Exp. 2, 0.4% CB decreased feed-gain ratio (P < 0.1), diarrhea score (P < 0.05), and increased duodenal, jejunal, and ileal villus height and jejunal villus height/crypt depth (P < 0.05). The 0.4% CB decreased the plasma tumor necrosis factor (TNF) α (P < 0.05) but increased ileal mucosa IL-10 and TLR2 mRNA expression (P < 0.05). Furthermore, 0.4% CB altered the microbial profile, with Bacillus and Ruminococcaceae UGG-003 at genus level and Lactobacillus casei and Parasutterella secunda at species level were higher than CON in colonic content (P < 0.05). CONCLUSIONS: Dietary C. butyricum supplementation had positive effects on growth of weaned piglets with less digestible diets. There was a tendency to reduce the feed-gain ratio, which could reduce feed costs in pig production. Moreover, C. butyricum decreased post-weaning diarrhea by improving the intestinal morphology, intestinal microflora profile, and immune function.